1981
DOI: 10.1103/physrevlett.47.460
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Tests of Realistic Local Theories via Bell's Theorem

Abstract: We have measured the linear polarization correlation of the photons emitted in a radiative atomic cascade of calcium. A high-efficiency source provided an improved statistical accuracy and an ability to perform new tests. Our

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
1,333
1
39

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,930 publications
(1,397 citation statements)
references
References 18 publications
24
1,333
1
39
Order By: Relevance
“…Shocking as it may be, our world is not of this kind. Statistical inequalities, such as e = 1/4, derived on the assumption that the values of unmeasured physical quantities do exist and commonly referred to as Bell's inequalities 33 , have been violated in a number of painstaking experiments 33,34,35,36,37,38,39,40,41,42,43,44 . We shall not dwell on the philosophical implications of this experimental fact (volumes have been written on the subject), but simply point out that it should be embraced by all those who worry about secrecy because what does not exist cannot be eavesdropped, and so it is much easier to keep secrets in a non-classical world.…”
Section: Less Reality More Securitymentioning
confidence: 99%
“…Shocking as it may be, our world is not of this kind. Statistical inequalities, such as e = 1/4, derived on the assumption that the values of unmeasured physical quantities do exist and commonly referred to as Bell's inequalities 33 , have been violated in a number of painstaking experiments 33,34,35,36,37,38,39,40,41,42,43,44 . We shall not dwell on the philosophical implications of this experimental fact (volumes have been written on the subject), but simply point out that it should be embraced by all those who worry about secrecy because what does not exist cannot be eavesdropped, and so it is much easier to keep secrets in a non-classical world.…”
Section: Less Reality More Securitymentioning
confidence: 99%
“…Evidently, he did not recognize the correlation of observables A (s) 1 and B (s) 2 as an ordinary observable, to be measured by means of coincidence measurements like the EPR-Bell ones performed e.g. by Aspect et al [42,43]. Instead, he followed EPR in taking for granted existence of the correlation of the observables already if only one of the observables is measured.…”
Section: Epr and Correspondencementioning
confidence: 99%
“…Thus, the maximal violation of Bell inequality in quantum mechanics has the extra √ 2 factor in the case of a pair of spins [16]. This violation was convincingly tested by Aspect et al [2,3] (see Figure 1) and the quantum entanglement was confirmed as a fundamental aspect of quantum mechanics. 1 To avoid confusion, the tensor product ⊗ is omitted below for simplicity.…”
Section: Bell Inequalitymentioning
confidence: 73%
“…In this case, we get the maximum value B 4 ∼ 1.45 (see Figure 3), then q ≥ (1.45) 2 2.1 and then log 2 2.1 1.07 > 1. Thus, we have shown that the violation of Bell inequalities increases exponentially with the number of modes to measure k. This indicates that some evidence that our universe has a quantum mechanical origin may survive in CMB data, even if quantum entanglement decays exponentially afterward due to decoherence.…”
Section: The Case Of a Non-bunch-davies Vacuummentioning
confidence: 78%
See 1 more Smart Citation